Surveillance of maternal antibodies against West Nile virus in chicken eggs in South‐West Germany. Issue 5 (26th February 2016) - Börstler, Jessica; Engel, Dimitri; Petersen, Mathis; Poggensee, Claudia; Jansen, Stephanie; Schmidt‐Chanasit, Jonas; Lühken, Renke
Abstract: Objective: The emergence of West Nile virus (WNV) in several European countries increases the risk of its introduction to Germany. This study evaluated a new method for WNV surveillance by testing for maternal antibodies in chicken eggs. Methods: A total of 1, 990 eggs were collected in 35 sampling sites in the south‐west of Germany and tested for WNV‐specific antibodies. Results: The results did not indicate evidence for WNV circulation in the study area. Conclusion: This work serves as a proof‐of‐concept that such a method is useful and a potential alternative to use of sentinel chicken for regular WNV surveillance.